2020
DOI: 10.15587/1729-4061.2020.209108
|View full text |Cite
|
Sign up to set email alerts
|

Development of a technique for the geometrical modeling of conjugated surfaces when determining the geometrical parameters of an engagement surface contact in kinematic pairs

Abstract: This paper reports a technique for constructing a geometric shape of the surface of contact between the interacting conjugated machine elements using computer technology. A subprogram has been developed in the MATLAB software package. The comprehensive solution to such problems is a certain scientific challenge and is of great importance when designing the kinematic pairs in mechanical engineering. The main systemic drawback in the construction of complex mechanisms is that the design process does not take int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
0
4
0
1
Order By: Relevance
“…From the coordinate arrays of the original and resulting curved surfaces, the coordinates of the intersection line are determined. The intersection line arrays will contain those values that are equal for the original and curved surfaces [9].…”
Section: Discussion Of the Results Of The Study Of An Invariant Metho...mentioning
confidence: 99%
See 1 more Smart Citation
“…From the coordinate arrays of the original and resulting curved surfaces, the coordinates of the intersection line are determined. The intersection line arrays will contain those values that are equal for the original and curved surfaces [9].…”
Section: Discussion Of the Results Of The Study Of An Invariant Metho...mentioning
confidence: 99%
“…The work [9] proposed a geometric method for determining interference based on the shape of the contact spatial surface of kinematic pairs and a cutting tool. The disadvantage is the following: for each intersection line it is necessary to calculate the coordinates using formulas specific to them; it is necessary to create an additional algorithm to determine which formula to use when determining the intersection line.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…A noteworthy study reported in [12] considered the contact surface of kinematic pairs. The noted techniques of constructing mated surfaces most often focus on a certain range of tasks that are successfully resolved under certain limitations.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…1-3). Given the confirmation from the system of equations (5) [12], and assuming that the curvilinear surface can be set by any other parametric equation, we modify the method of circular conversion in the following way. Ypr(i,j) = (Xp(i,j)-x0)*sin(Angle)+ +(Yp(i,j)-y0)*cos(Angle)+y0; end end…”
Section: T T Y Y T T Z Z C Tmentioning
confidence: 99%
“…Поставлену задачу вирішимо геометричним моделюванням конволютних гелікоїдів для практичного використання при проектуванні ріжучого інструменту і зубчастого зачеплення довільного профілю кінематичних пар. За допомогою комп'ютерних технологій розробимо геометричне моделювання криволінійної поверхні ріжучого інструменту на базі параметричного кінематичної гвинта [4,5].…”
unclassified